ÇOCUK YOĞUN BAKIM ÜNİTESİNDE YÜKSEK AKIŞLI NAZAL KANÜL OKSİJEN TEDAVİSİ ALAN ÇOCUKLARA UYGULANAN TERAPÖTİK OYUNUN ÇOCUKLARIN TEDAVİYE UYUM SÜRECİNDE KORKU VE ANKSİYETE DÜZEYİNE ETKİSİ - ÇETİN, KERİME DENİZ KILIÇ (Fırat Üniveristesi, 2025)
Yüksek akışlı nazal kanül oksijen tedavisinde çocuğa ısıtılmış ve nemlendirilmiş oksijen, nazal kanül takılarak verilmektedir. Çocuklar oksijen ve nazal kanülden rahatsız olabilmekte ve çıkarmak isteyebilmektedir. Bu durumda çocuklar anksiyete ve korku yaşayabilmektedir. Bu nedenle bu araştırma yüksek akışlı nazal kanül oksijen tedavisi alan çocuklarda terapötik oyunun tedaviye uyum sürecindeki korku ve anksiyete düzeyi ve davranışları üzerindeki etkiyi değerlendirmek amacı ile yapıldı. Bu araştırma, ön test son test kontrol gruplu deneysel bir çalışma olarak yapıldı. Araştırma Sivas ilinde bulunan kamu hastanesinin çocuk yoğun bakım ünitesinde Haziran-Aralık 2024 tarihleri arasında yapıldı. Araştırmanın örneklemini çocuk yoğun bakım ünitesinde yüksek akışlı nazal kanül oksijen tedavisi alan 96 (deney grubu=48, kontrol grubu=48) çocuk oluşturdu. Veriler, Tanıtıcı Bilgi Formu, Çocuk Korku Ölçeği, Çocuk Anksiyete Skalası-Durumluluk ve Çocuk Gözlem Formu ile toplandı. Deney grubundaki çocuklara yüksek akışlı nazal kanül oksijen tedavisinden önce terapötik oyun uygulandı. Verilerin değerlendirilmesinde; ki-kare analizi, fisher exact, bağımsız gruplar t-testi; tekrarlayan ölçümler için genel doğrusal model kullanıldı. Araştırmada deney grubundaki çocukların korku ve anksiyete düzeylerinin kontrol grubundaki çocuklara göre azaldığı ve aralarındaki fark istatistiksel olarak anlamlı olduğu belirlendi (p=0.000). Deney grubundaki çocukların tedavi sırasında nazal kanülü çıkarma, ağlama ve huzursuzluk gibi durum ve davranışlarının kontrol grubundakilere göre azaldığı ve gruplar arasındaki farkın istatiksel olarak anlamlı olduğu saptandı (p=0.000). Yüksek akışlı nazal kanül oksijen tedavisi alan çocuklarda terapötik oyunun korku ve anksiyete düzeyini azaltmada ve tedaviye uyum sürecindeki davranışlarını olumlu yönde etkilediği görülmektedir. Anahtar Kelimeler: Terapötik oyun, yüksek akışlı nazal kanül, çocuk, korku, anksiyete

In high-flow nasal cannula oxygen therapy, heated and humidified oxygen is given to the child through a nasal cannula. Children may be uncomfortable with the oxygen and nasal cannula and may want to remove it. In this case, children may experience anxiety and fear. Therefore, this study was conducted to evaluate the effect of therapeutic play on fear and anxiety levels and behaviors during the adaptation to treatment in children receiving high-flow nasal cannula oxygen therapy. This research was conducted as an experimental study with a pre-test post-test control group. The study was conducted in the pediatric intensive care unit of a public hospital in Sivas province between June and December 2024. The sample of the study consisted of 96 children (experimental group=48, control group=48) receiving high-flow nasal cannula oxygen therapy in the pediatric intensive care unit. Data were collected using the Descriptive Information Form, Child Fear Scale, Child Anxiety Scale-Conditioning and Child Observation Form. Children in the experimental group received therapeutic play before high-flow nasal cannula oxygen therapy. Chi-Square analysis, Fisher Exact, Independent Groups T-Test, General Linear Model for Repeated Measures were used in the evaluation of the data. In the study, it was determined that the fear and anxiety levels of the children in the experimental group decreased compared to the children in the control group and the difference between the groups was statistically significant (p=0.000). It was found that the conditions and behaviors of the children in the experimental group such as removing the nasal cannula, crying and restlessness during treatment decreased compared to those in the control group and the difference between the groups was statistically significant (p=0.000). In children receiving high-flow nasal cannula oxygen therapy, it is seen that therapeutic play has a positive effect on reducing the level of fear and anxiety and on their behaviors in the process of adaptation to treatment. Keywords: Therapeutic play, high flow nasal cannula, children, fear, anxiety
The effect of therapeutic play on the levels of fear and anxiety in children receiving high-flow nasal cannula oxygen therapy in the Pediatric Intensive Care Unit during their treatment adherence process
Keywords: Çocuk Sağlığı ve Hastalıkları